Highly Emissive Water‐Soluble Polysulfurated Pyrene‐Based Chromophores as Dual Mode Sensors of Metal Ions. Issue 7 (9th July 2020) - Villa, Marco; Roy, Myriam; Bergamini, Giacomo; Ceroni, Paola; Gingras, Marc
Abstract: Pyrene‐based materials have gained considerable attention as stimuli‐responsive chemical sensors. We designed a polysulfurated arene system based on a tetra(phenylthio)pyrene core decorated with four carboxylic acid units. Three different regioisomers, ortho, meta and para were studied in organic and aqueous solution. These systems are soluble in water at pH≥8 due to the deprotonation of carboxylic acids. The addition of metal ions cannot only quench the fluorescence of the central pyrene core, but also control the formation of three‐dimensional nanoscopic objects in a dual mode function. Several divalent metal ions were tested and compared. Addition of ethylenediaminetetraacetic acid (EDTA) disassembles the non‐emissive supramolecular system and restores the initial fluorescence of the pyrene core. Abstract : Complexation power : Three novel regioisomers of a tetrasulfurated pyrene with four carboxylic acids ( ortho, meta, para ) were designed to complex divalent metal ions and to generate supramolecular polymers in aqueous solution. Depending on the presence of metal ions, the initial fluorescence of the pristine molecule is quenched, while generating supramolecular structures, leading to a dual mode sensor based on changes in aggregation and emission.